Circadian rhythm affects the magnitude of contact hypersensitivity response in mice. Issue 9 (22nd April 2022) - Miyake, Toshiya; Egawa, Gyohei; Chow, Zachary; Asahina, Ryota; Otsuka, Masayuki; Nakajima, Saeko; Nomura, Takashi; Shibuya, Rintaro; Ishida, Yoshihiro; Nakamizo, Satoshi; Murata, Teruasa; Kitoh, Akihiko; et al.
Abstract: Background: The circadian rhythm controls multiple biological processes, including immune responses; however, its impact on cutaneous adaptive immune response remains unclear. Methods: We used a well‐established cutaneous type IV allergy model, contact hypersensitivity (CHS). We induced CHS using dinitrofluorobenzene (DNFB). Mice were sensitized and elicited with DNFB in the daytime or at night. Results: In mice, a nocturnally active animal, we found that ear swelling increased when mice were sensitized at night compared with in the daytime. In addition, cell proliferation and cytokine production in the draining lymph nodes (LNs) were promoted when sensitized at night. We hypothesized that these differences were due to the oscillation of leukocyte distribution in the body through the circadian production of adrenergic hormones. Administration of a β2‐adrenergic receptor (β2AR) agonist salbutamol in the daytime decreased the number of immune cells in blood and increased the number of immune cells in LNs. In contrast, a β2AR antagonist ICI18551 administration at night increased the number of immune cells in blood and decreased the number of immune cells in LNs. Accordingly, the severity of CHS response was exacerbated by salbutamol administration in the daytime and attenuated by ICI18551 administration at night. Conclusion: Our study demonstrated that the magnitude of adaptive CHS response depends on the circadian rhythm and this knowledge may improve the management of allergic contact dermatitis (ACD) in humans. Abstract : The severity of CHS response increases when mice were sensitized at night compared with those sensitized in the daytime. Cell proliferation and cytokine production in the draining lymph nodes are promoted in mice sensitized at night. Leukocyte distribution in the body shows diurnal oscillation.Abbreviations: CHS, contact hypersensitivity; CPM, counts per minute; DC, dendritic cell; DNFB, dinitrofluorobenzene; IFN‐γ, interferon‐γ